Level Down: Using Games as a Teaching Tool for Low-Level Computer Science - Wright, Hannah (Science, 2021)
Game-based learning has had promising results for a variety of different topics; however, for computer science education in particular, its applications have mostly focused on high-level concepts such as program flow and the control structures that modify it. Considering that students are known to struggle with low-level topics, the goal of this thesis is to level down game-based learning by applying it to lower-level concepts—this is accomplished by designing, building, and evaluating two original games. The first game is the physical card game Mermaids and Narwhals, which is meant to teach binary manipulations such as shifts and rotations with broader applications in computational thinking; it was evaluated through a gameplay simulation that modelled the game's behaviour under different conditions. The second game is Binary Bubbles, which is a digital bubble shooter game designed to help students practice their Boolean/bitwise logic operations; this game was evaluated through a large two-group, pre-test post-test survey. Overall, this thesis contributes to a promising area of research that has been relatively unexplored in related literature.